Pets' party - Baglio, Ben M.; Howard, Paul. (New York : Scholastic, 2001)
Mandy decides to have a party for neighborhood pets.
"A Little Apple paperback".
540
Accelerated Reader AR
Keywords: Animals -- Fiction